1994
DOI: 10.1111/j.1365-2249.1994.tb06116.x
|View full text |Cite
|
Sign up to set email alerts
|

The IgE and IgG antibody responses to aerosols of Nephrops norvegicus (prawn) antigens: the association with clinical hypersensitivity and with cigarette smoking

Abstract: SUMIVIARYRaised levels of serum IgE antibodies to prawn antigens were found in 15 of 26 seafood factory process workers with respiratory symptoms and in one of 26 case-matched asymptomatic controls (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…There are conflicting results on the relationship between smoking and OA in general27 including in workers exposed to crustaceans. Smoking has been shown to be associated with OA in snow crab-processing workers (p<0.05)2 and with increased specific IgE production among prawn processors (OR = 2.4) 28…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting results on the relationship between smoking and OA in general27 including in workers exposed to crustaceans. Smoking has been shown to be associated with OA in snow crab-processing workers (p<0.05)2 and with increased specific IgE production among prawn processors (OR = 2.4) 28…”
Section: Discussionmentioning
confidence: 99%
“…Atopy has been associated with an increased risk of sensitization in workers exposed to a number of occupational allergens including; acid anhyrides; [Welinder et al, 2001] bakery allergens; [Houba et al, 1998] castor and green coffee beans; [Osterman et al, 1982; Romano et al, 1995] enzymes; [Zentner et al, 1997; Cullinan et al, 2000] laboratory animals; [Cullinan et al, 1999] and shellfish [Cartier et al, 1984; McSharry et al, 1994]. Our study demonstrated that atopy is also strongly associated with sensitization to soybean, with atopic workers having an approximately 35‐fold increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, Douglas et al were unable to demonstrate atopy as a risk factor for occupational asthma among fish (salmon) processing workers (Douglas et al, 1995). Smoking, on the other hand has been demonstrated in a study among prawn processors as an independent risk factor for increased specific IgE production (OR=2.4) (Mc Sharry et al, 1994). A significant association between serum antibodies and smoking was also demonstrated among salmon processors with smokers having higher IgE and non-smokers higher IgG levels (Douglas et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Atopy has been more consistently associated with sensitization to shellfish (clam, shrimp, crab, prawn and cuttlefish) in particular (Desjardins et al, 1995; Cartier et al, 1984; Gaddie et al, 1980; Olszanski et al, 1997). Smoking has been demonstrated in one study among prawn processors as an independent risk factor for increased specific IgE production (OR=2.4) (Mc Sharry et al, 1994). A detailed study of these host factors in fish processors has not been conducted.…”
mentioning
confidence: 99%